2020
DOI: 10.48550/arxiv.2008.12417
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prospects for nuclear spin hyperpolarisation of molecular samples using nitrogen-vacancy centres in diamond

J. -P. Tetienne,
L. T. Hall,
A. J. Healey
et al.

Abstract: After initial proof-of-principle demonstrations, optically pumped nitrogen-vacancy (NV) centres in diamond have been proposed as a non-invasive platform to achieve hyperpolarisation of nuclear spins in molecular samples over macroscopic volumes and enhance the sensitivity in nuclear magnetic resonance (NMR) experiments. In this work, we model the process of polarisation of external samples by NV centres and theoretically evaluate their performance in a range of scenarios. We find that average nuclear spin pola… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 78 publications
0
3
0
Order By: Relevance
“…In pioneering work by Jacques, et al 28 , this effect was demonstrated under 532 nm laser illumination by facilitating a cross-relaxation process between the polarised electron spin and its intrinsic 15 N nuclear spin in the electronic excited state, due to the excited state level anticrossing (ESLAC) at ∼ 500 G. The extent of polarisation was inferred by using optically detected magnetic resonance (ODMR, 29 ) to monitor the intensity of its electron paramagnetic resonance (EPR) lines, and was found to be in excess of 99% for the 15 N nucleus, and in excess of 90% when similarly applied to a strongly coupled 13 C nucleus in the first coordination shell of the NV. This effect was independently verified in ref.…”
Section: Dynamic Nuclear Polarisation With Solid-state Electron Spinsmentioning
confidence: 98%
See 2 more Smart Citations
“…In pioneering work by Jacques, et al 28 , this effect was demonstrated under 532 nm laser illumination by facilitating a cross-relaxation process between the polarised electron spin and its intrinsic 15 N nuclear spin in the electronic excited state, due to the excited state level anticrossing (ESLAC) at ∼ 500 G. The extent of polarisation was inferred by using optically detected magnetic resonance (ODMR, 29 ) to monitor the intensity of its electron paramagnetic resonance (EPR) lines, and was found to be in excess of 99% for the 15 N nucleus, and in excess of 90% when similarly applied to a strongly coupled 13 C nucleus in the first coordination shell of the NV. This effect was independently verified in ref.…”
Section: Dynamic Nuclear Polarisation With Solid-state Electron Spinsmentioning
confidence: 98%
“…For example, in the case of a 14 NV coupled to proton spins, only the after-GSLAC interaction is observed due to the avoided crossing before the GSLAC, however both transitions are observed for nuclei with smaller gyromagnetic ratios. In the case of 15 NV, no transition frequency exists below roughly 3 MHz, making it suitable for NV-DNP of 1,3 H and 19 F spins, but little else (detailed discussions of these considerations may be found in refs. 39,41).…”
Section: Single-spin Target Environmentsmentioning
confidence: 99%
See 1 more Smart Citation